Statistical Characteristics of the Daily Max of Wind Speed in Kakheti in 2017-2019 - Amiranashvili, Avtandil G.; Chikhladze, Victor A.; Gvasalia, Gvantsa D.; Loladze, Davit A. (Journals of Georgian Geophysical Society, 2020)
The statistical analysis of the daily maximum speed of wind (W) for 13 points of Kakheti in the period from 1 January 2017 through 31 December of 2019 is represented. In particular, the following results are obtained: mean monthly and seasonal (warm and cold half-years, year) values of W for all stations during entire period of observations are calculated; it is shown that the distributions of mean monthly values of W in the territory of Kakheti has the uneven nature and changes from 0.7 m/sec (Tsnori, November) to 9.5 m/sec (Sagarejo, June); the map of the distribution of mean annual values of W in the territory of Kakheti is given; repetition of daily values of W for all points of Kakheti in accordance with the Beaufort Wind Scale is studied; it is shown that the value of the linear correlation coefficient R between the stations in terms of all daily values of W on the average compose 0.45 and change from 0.15 to 0.83, for the cold half-year - 0.54 (it changes from 0.26 to 0.87), for the warm half-year - 0.36 (it changes from 0.03 to 0.78); the dependence of the linear correlation coefficient between the stations by values of W from the distance between them is studied (with an increase in the distance between the stations value of R diminishes in the correspondence with the power function); the dependence of W on the height of the stations arrangement on the average in the year, into the cold and warm half-years is studied.